The Mystical Union Between Christ and His Brides: Devotional Prints as a Source for Catholic Women’s History - Verheggen, Evelyne (Early Modern Low Countries, 2025)
Hundreds of (semi-)religious women, so-called kloppen and Beguines, lived in early modern Amsterdam, many of them in a community at the Begijnhof in the city centre. This case study analyses, via an emblematically painted devotional print with a calligraphed poem on the verso, how they collectively visualised and experienced their communion with the bridegroom Christ. A significant proportion of the Dutch population remained Catholic throughout the seventeenth century. As monasteries were forbidden, many Catholic women turned to a religious life ‘in the world’, an act which was tolerated by the Reformed authorities. Such a life offered women the chance to develop independently, self-willed, and intellectually outside marriage, a path that was cut off for Protestant women after the Reformation. For their spiritual life, these Catholic women made intensive use of devotional prints, which they sometimes augmented with friendly poems or prayers on the reverse. Prayers were also exchanged for the salvation of deceased fellow sisters. Sometimes, texts and notes on the prints and drawings were inspired by songs that were included in their prayer books. These devotionalia thus provide an interesting, as yet unknown source for research into the daily life, practised spirituality, and agency of semi-religious women in the Low Countries.